MAXIMIZING THE USE OF WHATSAPP IN ENGLISH REMOTE LEARNING TO PROMOTE STUDENTS’ ENGAGEMENT AT MADURA - Eva Nikmatul Rabbianty; abd Ghofur; Abdul Wafi (LET: Linguistics, Literature and English Teaching Journal, 2021)
There are ample remote learning platforms to be used and obviously each of them has strengths and weaknesses. However, based on a survey, WhatsApp becomes the top choice to be used by students in Madura for some reasons; this is a case study on maximizing the use of Whatsapp to promote students’ engagement in English remote learning. The data are collected through Google form questionnaire and in-depth interview via WhatsApp voice notes. The subjects are English lecturers and higher education students of English department from several Universities in Madura whom are volunteers to be taken as sample. The result showed that exploring the various features of WhatsApp, blending various learning platforms to WhatsApp and lecturer’s creativity in maximising the use of WhatsApp enable to promote the students’ engagement toward the English remote learning. Thus, it is suggested to maximize the use of WhatsApp as to promote the students’ engagement towards the English Remote Learning.